A Brief Report on Scale Independent Quantum Cosmology - Seshavatharam, U. V. S; Lakshminarayana, S (Review of Advances in Physics Theories and Applications, 2015)
In the evolving universe, cosmic thermal energy density is always directly proportional to the critical mass-energy density. At any time, the product of cosmic ‘critical density’ and ‘critical Hubble volume’ can be called as the ‘critical mass’ of the evolving universe. With reference to Mach’s principle, cosmic ‘critical density’, ‘critical volume’ and ‘critical mass’ can be considered as the quantified back ground dynamic properties of the evolving universe. With reference to Planck mass, Hubble constant connected with big bang and critical density connected with big bang- both can be defined. With ‘cosmologically reinforcing hydrogen atom’ concept, observed cosmic redshift and super novae dimming both can be reinterpreted in a new approach. To understand the ground reality of cosmic rate of expansion, accuracy of the current methods of estimating the magnitudes of current Hubble’s constant and current CMBR temperature must be improved.